Drosophila sticky/citron kinase is a regulator of cell-cycle progression, genetically interacts with Argonaute 1 and modulates epigenetic gene silencing. - Sweeney, S.J.; Campbell, P.; Bosco, G. (Genetics, 2008)
The sticky/citron kinase protein is a conserved regulator of cell-cycle progression from invertebrates to humans. While this kinase is essential for completion of cytokinesis, sticky/citron kinase phenotypes disrupting neurogenesis and cell differentiation suggest additional non-cell-cycle functions. However, it is not known whether these phenotypes are an indirect consequence of sticky mutant cell-cycle defects or whether they define a novel function for this kinase. We have isolated a temperature-sensitive allele of the Drosophila sticky gene and we show that sticky/citron kinase is required for histone H3-K9 methylation, HP1 localization, and heterochromatin-mediated gene silencing. sticky genetically interacts with Argonaute 1 and sticky mutants exhibit context-dependent Su(var) and E(var) activity. These observations indicate that sticky/citron kinase functions to regulate both actin-myosin-mediated cytokinesis and epigenetic gene silencing, possibly linking cell-cycle progression to heterochromatin assembly and inheritance of gene expression states.